States, American Indian Nations, and Intergovernmental Politics - Flaherty, Anne F. Boxberger, author. Merrimack College, USA.
1 online resource (xiv, 227 pages)
Keywords: American Indian nations are sovereign political entities within the United States. They have complex relationships with the federal government and increasingly with state governments. Regulatory conflict between Native nations and states has increased as Native nations have developed their own independent economies and some states have sought to assert their control over reservation territory. This book explores the intergovernmental conflict between Native nations and states, with a focus on the tension over the enforcement of state cigarette taxes for on-reservation sales. Anne F. Boxberger Flaherty asks: when do states and Native nations come to agreement, when do they disagree, and why are states sometimes willing to extend great efforts to assert their taxes on reservations??Flaherty uses a multi-method approach, with a historical review of expanding state involvement on reservations, a quantitative analysis of state enforcement of cigarette taxes on reservations, and a qualitative analysis of several specific case studies, including the potential for intergovernmental conflict over marijuana cultivation and sales on reservations to answer these questions.?This book will be interest to scholars and researchers of Indigenous Politics, Native American Indian Politics, State Politics, and Intergovernmental Politics.